Prevalence and trends in tobacco use among adolescents aged 13–15 years in 143 countries, 1999–2018: findings from the Global Youth Tobacco Surveys. (April 2021) - Ma, Chuanwei; Xi, Bo; Li, Zilin; Wu, Han; Zhao, Min; Liang, Yajun; Bovet, Pascal
Summary: Background: Tobacco use is a leading preventable cause of morbidity and mortality worldwide. Little is known about recent prevalence and trends in tobacco use among adolescents globally. We aimed to assess the recent global prevalence of tobacco use in young adolescents and the secular trends in prevalence between 1999 and 2018. Methods: We used the most recent Global Youth Tobacco Surveys data on adolescents aged 13–15 years from 143 countries or territories that had done at least one survey between Jan 1, 2010, and Dec 31, 2018, to assess the recent prevalence of tobacco use; and data from 140 countries that had done two or more surveys between Jan 1, 1999, and Dec 31, 2018, to assess the trends in the prevalence of tobacco use. Findings: 530 234 adolescents were included from the 143 countries that had done at least one survey between 2010 and 2018. 1 192 312 adolescents were included from the 140 countries that had done two or more surveys between 1999 and 2018. The most recent global prevalence of cigarette smoking was 11·3% (95% CI 10·3–12·3) in boys and 6·1% (5·6–6·6) in girls, based on cigarette smoking on at least 1 day during the past 30 days, 6·0% (5·5–6·6) and 2·6% (2·4–2·9) based on smoking on at least 3 days, and 4·2% (3·8–4·6) and 1·6% (1·4–1·8) based on smoking on at least 6 days. The most recent prevalence of the use of tobacco products other than cigarettes (eg, chewing tobacco, snuff, dip, cigars, cigarillos, pipe, electronic cigarettes) on at least 1 day during the past 30 days was 11·2% (9·9–12·6) in boys and 7·0% (6·4–7·7) in girls. The most recent prevalence of any tobacco use on at least 1 day during the past 30 days was 17·9% (16·1–19·6) in boys and 11·5% (10·5–12·4) in girls. The prevalence of cigarette smoking on at least 1 day during the past 30 days decreased between the first and last surveys in 80 (57·1%) of 140 countries, was unchanged in 39 countries (27·9%), and increased in 21 countries (15·0%). However, the prevalence of the use of tobacco products other than cigarettes was unchanged or increased in 81 (59·1%) of 137 countries. Interpretation: The global prevalence of tobacco use among adolescents aged 13–15 years was substantial. Although the prevalence of cigarette smoking decreased over time in the majority of countries, the prevalence of the use of other tobacco products increased or did not change in the majority of countries during the past two decades. These findings re-emphasise the need to strengthen tobacco control efforts among young adolescents globally. Funding: Shandong University.